Scaling with deformation in probable p-wave halo 34Na. (December 2020) - Manju,; Singh, Jagjit; Shubhchintak,; Chatterjee, R.
Abstract: We investigate the electric dipole response of 34 Na, a probable p -wave one-neutron halo nucleus, lying in the "island of inversion" and having a deformed structure. We use a semi-analytic approach to probe the dipole response and further compare the results obtained from a post form finite-range distorted wave Born approximation theory of Coulomb breakup. The effects of deformation are figured out on the peak positions of the electric dipole strength distribution which further constraint the one-neutron separation energy of the deformed projectile and it leads to a two-dimensional scaling of total B ( E 1) strength with parameters: separation energy and deformation.